Pesantren Students’ Ideal Selves and Motivation to Learn English as A Foreign Language - Afidah Iftitah Setya Amalia; Kunsarwani Kunsarwani; Achmad Farid; Nailul Fauziyah (Universitas Pesantren Tinggi Darul Ulum Jombang (Unipdu), 2022)
Anecdotal evidence suggests that some students from pesantren (Islamic boarding school) show negative view on English. They seem to study English because it is an obligation and to meet the passing grade. This paper aims to find out how motivated students are to learn English, and to reveal whether their ideal selves affect their motivation in learning English. Using a theoretical framework proposed by (Dörnyei and Ushioda, 2009), and by adopting a questionnaire from previous research by (Farid & Lamb, 2020), this study seeks to find how pesantren school students’ motivation to learn English is connected to their ideal selves. Data from the questionnaire that was administered to 103 participants were analyzed using Spearman Correlation in SPSS. The results show that there is a good correlation between motivation and ideal selves. This finding is also supported by students’ responses to open-ended questions that were designed to reveal participants’ plans after graduating. This research also revealed that pesantren students’ motivation is quite low, and their ideal selves affect their motivation in learning English.